Should we expand the indications for varicocele treatment? - Vakalopoulos, Ioannis; Kampantais, Spyridon; Lymperi, Stefania; Grivas, Nikolaos; Ioannidis, Anastasios; Mykoniatis, Ioannis; Nikolaou, Vassilios; Dimitriadis, Georgios (Translational Andrology and Urology; Vol 6, No 5 (October 26, 2017): Translational Andrology and Urology (Management of Penile Cancer), 2017)
Current guidelines suggest that treatment of varicocele should be considered in patients with clinically palpable disease and abnormal semen parameters. However, the clinicians are often challenged with the decision whether to treat varicocele in patients with testicular pain or low testosterone levels. Moreover, varicocele is highly associated with DNA fragmentation due to the oxidative stress and it has been demonstrated that surgical repair of varicocele ameliorates oxidative stress markers and consequently the sperm DNA integrity. These new markers could have an adjunctive role to standard semen parameters especially when normal semen analysis is found in adult men with conventional methods. This review presents a contemporary overview of the rationale for varicocele treatment, as well as of the relationship between varicocele and other novel parameters such as DNA fragmentation index and reactive oxygen species. We will also discuss data from several recent series demonstrating that surgical treatment and especially microsurgical approach could resolve testicular pain, increase testosterone levels and fertility rate both in patients with non-obstructive azoospermia as well as in normozoospermia men. The correlation with progressive testicular failure will be also examined. We hope that this overview will provide clinicians with an evidence-based approach to managing these unanswered and conflicting topics.